2002
DOI: 10.1002/cne.10248
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of spinal interneurons induced by sciatic nerve axotomy in the neonatal rat is counteracted by nerve growth factor and ciliary neurotrophic factor

Abstract: We have previously shown that not only motoneurons and dorsal root ganglion cells but also small neurons, presumably interneurons in the spinal cord, may undergo apoptotic cell death as a result of neonatal peripheral nerve transection in the rat. With the aid of electron microscopy, we have here demonstrated that apoptosis in the spinal cord is confined to neurons and does not involve glial cells at the survival time studied (24 hours). To define the relative importance of the loss of a potential target (moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
2
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 56 publications
(65 reference statements)
1
33
2
7
Order By: Relevance
“…6). Scale bars ϭ 100 m. Oliveira et al, 2002). Furthermore, NGF and NT3 gene knockout mice show severe neuronal deficits and an early postnatal death (Conover and Yancopoulos, 1997).…”
Section: Survival Analysis Of Neonatal Drg Neurons Co-cultured With Smentioning
confidence: 98%
“…6). Scale bars ϭ 100 m. Oliveira et al, 2002). Furthermore, NGF and NT3 gene knockout mice show severe neuronal deficits and an early postnatal death (Conover and Yancopoulos, 1997).…”
Section: Survival Analysis Of Neonatal Drg Neurons Co-cultured With Smentioning
confidence: 98%
“…The neuroprotective effects of CNTF following SCI and other CNS disease have long been confirmed by previous researchers (Linker et al, 2002;Oliveira et al, 2002;Ye et al, 2004;Lu et al, 2009). Studies have shown that intracerebroventricular or intrathecal infusion, but not intravenous or local injection, is more effective at reversing neuronal deficits (Meazza et al, 1997).…”
Section: Discussionmentioning
confidence: 74%
“…Previous investigation has shown that CNTF can rescue motoneurons from apoptosis induced by sciatic nerve axotomy (Oliveira et al, 2002), and intrathecal infusion of exogenous CNTF following SCI can reduce tissue damage, protect the rubrospinal descending tracks, and enhance the functional recovery of adult rats (Ye et al, 2004).…”
mentioning
confidence: 99%
“…Such cellular loss has been related to the interruption of trophic support provided by target cells (1). However, the exogenous administration of neurotrophic molecules can prevent the death of neurons after peripheral nerve sectioning during the neonatal period (2)(3)(4). The ciliary neurotrophic factor (CNTF), a cytokine produced by Schwann cells, is capable of protecting the axotomized motoneurons when CNTF increases Bcl-2/Bax heterodimerization www.bjournal.com.br administered systemically in neonatal rodents (2)(3)(4).…”
mentioning
confidence: 99%
“…However, the exogenous administration of neurotrophic molecules can prevent the death of neurons after peripheral nerve sectioning during the neonatal period (2)(3)(4). The ciliary neurotrophic factor (CNTF), a cytokine produced by Schwann cells, is capable of protecting the axotomized motoneurons when CNTF increases Bcl-2/Bax heterodimerization www.bjournal.com.br administered systemically in neonatal rodents (2)(3)(4). This neuroprotective action of CNTF is considered to be due to the inhibition of apoptosis (4,5), while the effectiveness of systemic administration of CNTF may be due to its ability to cross the blood-brain barrier by a saturable transport system (6).…”
mentioning
confidence: 99%